Real-Time User-Service Centric Historical Trust Model Based Access Restriction in Collaborative Systems with Blockchain Public Auditing in Cloud - Kumar, N. Vel Murugesh; Raju, D. Naveen; PV, Gopirajan; Subhashini, P. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The recent collaborative systems works over the cloud environment which is being encouraged by various service providers in reality. The organizations maintain numerous data in cloud which has been accessed and shared by various users of the environment. The service provider has the responsibility in maintaining the originality of the data and maintaining the security of the data. To enforce both of them, various access restriction and public auditing schemes are available. Number of approaches uses different features of user as well as service. However they suffer to achieve expected performance in data security and public auditing. To handle this issue, a novel real-time User-Service Centric Historical Trust Model with Blockchain Public Auditing (USHTM-BPA) is presented in this article. The method computes User Centric Trust Score (UCTS) and Computes Service Centric Trust Score (SCTS) to measure Trust Weight for the user towards secure access restriction. Further, the method adapts Feature Level Blockchain Public Auditing (FLBPA) which measures feature centric trusted access score (FCTAS) in restricting illegal access to improve data security in public auditing. The proposed method improves the performance of public auditing in collaborative systems and improves data security in cloud.